2019
DOI: 10.1002/aic.16840
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐based reactor design for the continuous production of polymeric nanoparticles

Abstract: Polymeric nanoparticles (NPs) are versatile and effective drug delivery systems (DDS) that can be produced via nanoprecipitation of block copolymers. Yet, translation into clinical products has been limited. Thus, methods for NP production that enable rapid formulation screening and continuous production are needed. Toward this end, we engineered a coaxial jet mixer (CJM) for controlled and continuous nanoprecipitation in flow. The CJM enabled continuous assembly of poly(ethylene glycol)-block-polylactide NPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 60 publications
(86 reference statements)
0
40
0
Order By: Relevance
“…Ultrapure deionized water (dH 2 O) was freshly filtered using a Milli-Q IQ 7000 from Merck Millipore (CH). All components of the coaxial jet mixer were purchased from BGB Analytik (CH) or Cole-Parmer (US) and are listed in detail in our recent work (Bovone et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ultrapure deionized water (dH 2 O) was freshly filtered using a Milli-Q IQ 7000 from Merck Millipore (CH). All components of the coaxial jet mixer were purchased from BGB Analytik (CH) or Cole-Parmer (US) and are listed in detail in our recent work (Bovone et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The CJM design was based on similar devices used for inorganic particle synthesis and a recently developed device from our group for the flow-based production of polymeric nanoparticles (Baber et al, 2015;Bovone et al, 2019). The CJM was assembled from off-the-shelf components within minutes.…”
Section: Flow-based Nanoparticle Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…An extensive effort is required to manufacture degradable polymer particles with defined sizes through suitable control of their production process, optimization of the mixing conditions, and increased mass transfer between the two phases [18,19]. Previous studies demonstrated that these conditions are provided by applying microfluidic devices, which improve the control of the size and size distribution of particles [17,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%